(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2022)
This study focuses on William Chang’s ecclesiological research: "Doing Theology of Peace in the Middle of Conflict". There are two objectives of this research. First, to investigate the roots and sources of conflicts that have occurred in West Kalimantan, and the second is to offer a peaceful theology method proposed by William Chang to readers in order to resolve and anticipate the emergence of similar conflicts. This research has its context in West Kalimantan. The reason why the author chose West Kalimantan as the object of research is firstly because West Kalimantan has experienced bloody and deadly conflicts that have resulted in a loss of peace there. In such a situation, the Church is called to proclaim and maintain the order of peaceful life as mandated by Christ. The method used in this research is qualitative research methods. Here priority is given to research related to the results of previous research on the conflicts in West Kalimantan. Furthermore, the writer presents what the Church teaches regarding how to respond to social problems. Departing from these two theses, the writer then conducts a critical analysis by comparing it with the theological methods offered by William Chang. After going through a series of analyzes, this research finds that William Chang’s method provides a contextual theological offer for the people of West Kalimantan.